Development Of Statistical Model Estimating Biological Age - Karan Shivaji Raje, Dr. Satish V. Kakade, Dr. Sujata V. Patil (International Journal of Advanced Science and Technology, 2020)
Body age i.e. Biological age, also called physiological age, is a measure of how well or poorly his/her body is functioning relative to his/her actual calendar age. Very little and sporadic research work is available on Biological age. The aim of the present study was to generate a model predicting biological age and to identify modifiable health parameters that help in equalizing chronological age and biological age. The cross sectional study was carried out in the residents of village Khubi, Taluka Karad of Satara district, Maharashtra. Total 225 inhabitants participated in the study. Of these 94 (41.8%) were male respondents and 131 (58.2%) were female respondents. The mean and median age of male respondents was 45.2years and 46.5years, respectively, with SD 17.2years while the mean and median age of female respondents was 43.9years 42years, respectively, with SD 14.5years. The mean age of male and female respondents was similar. The mean biological age of males was 45.8years with SD 12.8years. The mean biological age of females was 48.2years with SD 14.4years. Significantly associated variables with difference in actual age and biological age were age, marital status, sex, type of work, occupation, BMI, diet, Yoga and swimming practices, habit of tobacco chewing and tobacco mishry use, and body fat. Logistic regression revealed the age earlier than 60 years, no habit of tobacco chewing, being housewife or serviceman, body fat above normal range and increasing BMI found contributors for higher biological age as compared to actual age. The developed logistic regression model may be useful in advising individuals along with clinical findings